DISEASES OF THE MUCOUS MEMBRANE OF THE ORAL CAVITY: A COMPREHENSIVE EXPLORATION - Soataliyev Asadbek; G.E.Tastanova (Scholar Express Journals, 2023)
This article provides a comprehensive overview of diseases affecting the mucous membrane of the oral cavity. It explores various conditions, their etiology, clinical manifestations, and potential complications. The article aims to enhance understanding among healthcare professionals, researchers, and the general public about the importance of oral mucosal health and the management of associated diseases
Keywords: Oral mucosa; Oral diseases; Mucous membrane